Reducing inequalities: Toward the development of a market for income inequality. (1st February 2020) - Husted, Bryan W.; Salazar, José
Abstract: The objective of this study is to propose the development of a market for income inequality by specifying a firm's contribution to income inequality and outlining a simple model to find the equilibrium price for a given target of income inequality reduction. The paper reviews the concepts of firm heterogeneity and externalities in relation to income inequality. It then proposes a model by establishing income inequality reduction targets for a population of firms, presenting a marginal income inequality reduction cost curve, and matching demand and supply to derive the equilibrium price, and ends by simulating a market for income inequality reduction using data from a sample of fifteen firms. This paper shifts the focus of income inequality research and policy to the firm and proposes a market-based mechanism for firms to reduce income inequality. Highlights: Lower pay differentials in and between firms leads to lower income inequality, economic growth, and ecological awareness. A market for income inequality allowances rewards firms with less income inequality and punishes ones with more inequality. We extend the externalities framework to include the externalities of income inequality caused by firm decisions.